2017
DOI: 10.1016/j.pharep.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in schizophrenia

Abstract: Many psychopathological symptoms, including schizophrenia, can be associated with magnesium metabolism disturbances. In the literature, contradictory data exist regarding magnesium levels in patients with this disorder. However, this situation might be caused by determination of extracellular concentration of magnesium; although, this is mainly an intracellular ion. There are no data concerning determination of the ionized fraction of magnesium in patients with schizophrenia, while the ionized fraction represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Serum ionized magnesium levels correlate with the level of cognitive function, while total serum magnesium levels do not [21]. As emerging evidence suggests that several psychopathological states, including schizophrenia, may be associated with metabolic changes involving Mg, supplementation with this required element is being investigated as an adjuvant therapy for some mental health conditions [120]. Low Mg levels along with high aluminum levels are consistently seen in Parkinson's disease and are believed to contribute to the pathogenesis of this disease [121].…”
Section: Resultsmentioning
confidence: 99%
“…Serum ionized magnesium levels correlate with the level of cognitive function, while total serum magnesium levels do not [21]. As emerging evidence suggests that several psychopathological states, including schizophrenia, may be associated with metabolic changes involving Mg, supplementation with this required element is being investigated as an adjuvant therapy for some mental health conditions [120]. Low Mg levels along with high aluminum levels are consistently seen in Parkinson's disease and are believed to contribute to the pathogenesis of this disease [121].…”
Section: Resultsmentioning
confidence: 99%
“…Their imbalance is able to interfere with the homeostasis, which has showed a key impact on the neurodegenerative and neuropsychiatric disorders, such as Parkinson's disease, Alzheimer's disease and schizophrenia 26 . Multiple studies have investigated the relationship between Mg and schizophrenia 27 . A significantly lower intraerythrocyte total Mg concentration has been observed in drug-naïve paranoid schizophrenic patients 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The above epidemiological findings have also been supported by the studies of biological mechanisms. In particular, it has been reported that Mg reduces glutamate release and interacts with NMDA receptors 28 , enhancing the GABAergic system 31 , acting as a natural inhibitor of excitotoxicity receptors, and thus preventing neuronal death and the development of schizophrenia 27 . Similar to Mg, a significantly lower level of serum Ca in schizophrenic patients has also been suggested 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A variety of neuromuscular and psychiatric symptoms, including depression, was reported in dysregulation of magnesium homeostasis [2,3,5]. Although the antidepressant activity of magnesium is mostly ascribed to the activity of the NMDA receptor, the mechanism of the antidepressant effect of magnesium is not yet fully understood [2].…”
Section: Resultsmentioning
confidence: 99%
“…Dysfunction of the prefrontal cortex occurs in many neuropsychiatric diseases. Some of these, such as depression, schizophrenia, mania, or anxiety disorders, may accompany magnesium and calcium homeostasis dysregulation [1][2][3][4][5]. Neuronal excitability is controlled by the activity of ion channels.…”
Section: Introductionmentioning
confidence: 99%